2005
DOI: 10.1111/j.1469-8137.2005.01493.x
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric nitrogen dioxide gas is a plant vitalization signal to increase plant size and the contents of cell constituents

Abstract: Summary We report the unexpected novel finding that exogenously supplied atmospheric NO2 at an ambient concentration is a plant vitalization signal to double shoot size and the contents of cell constituents. When seedlings of Nicotiana plumbaginifolia were grown for 10 wk under natural light and irrigation with 10 mm KNO3 in air containing (+NO2 plants) or not containing (–NO2 plants) 15NO2 (150 ± 50 ppb), shoot biomass, total leaf area, and contents per shoot of carbon (C), nitrogen (N), sulphur (S), phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
39
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 28 publications
5
39
0
Order By: Relevance
“…Besides the involvement of NO 2 in protein tyrosine nitration, an important posttranslational protein modification, 13 the metabolism of NO 2 in plants has also been reported. 1 Although more than half a dozen NO production pathways or routes 14 exist in plants, and many studies have reported on NO 2 emission by plants, in vivo biosynthetic pathways for NO 2 are largely unexplored, other than reports on the enzymatic production of NO 2 . 15 However, in vitro production of NO 2 via single-electron oxidations of nitrite by hemeproteins such as horseradish peroxidase and leukocyte peroxidases, Arabidopsis hemoglobins, and human hemo/myoglobins have been demonstrated (Shapiro 2005, 13 and references therein).…”
Section: Genes Involved In No 2 Control Of Organ Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Besides the involvement of NO 2 in protein tyrosine nitration, an important posttranslational protein modification, 13 the metabolism of NO 2 in plants has also been reported. 1 Although more than half a dozen NO production pathways or routes 14 exist in plants, and many studies have reported on NO 2 emission by plants, in vivo biosynthetic pathways for NO 2 are largely unexplored, other than reports on the enzymatic production of NO 2 . 15 However, in vitro production of NO 2 via single-electron oxidations of nitrite by hemeproteins such as horseradish peroxidase and leukocyte peroxidases, Arabidopsis hemoglobins, and human hemo/myoglobins have been demonstrated (Shapiro 2005, 13 and references therein).…”
Section: Genes Involved In No 2 Control Of Organ Sizementioning
confidence: 99%
“…Atmospheric NO and NO 2 have long been recognized as either detrimental or beneficial for plant development. 1,2 However, the molecular mechanisms of action underlying the effects have remained elusive. The 2 nitrogen oxide species readily interconvert in vivo, 3 and in vitro, 4 which suggests that there are similarities in their effects on plants.…”
mentioning
confidence: 99%
“…[25][26][27] Nitrogen analyses of gaseous 15 NO 2 -fed Arabidopsis plants have indicated that the contribution of NO 2 to total plant nitrogen is minor (>5%), and that NO 2 may function as a signal rather than a nutrient. 27 We also reported that some NO 2 -derived nitrogen is converted into oxidized nitrogen compounds, such as nitro and nitroso compounds.…”
mentioning
confidence: 99%
“…After washing the membrane two times in wash buffer, the immunopositive spots were visualized using a Western Blot Chemiluminescence Reagent Plus (NEN Life Science, MA, USA) and VersaDoc 5000 imaging system (Bio-Rad). (Takahashi et al 2005). Leaves were harvested from the upper (1st to 4th leaves from the shoot apex) and middle (5th to 8th leaves) part of each plant.…”
Section: Western Blot Analysismentioning
confidence: 99%